2021
DOI: 10.3390/educsci11110660
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Training Future Teachers during the COVID-19 Pandemic: A Case from TNPU

Abstract: This article describes the experience of the communicative competence formation of future teachers in a blended form of education as a dominant one in the period of the COVID-19 pandemic. The main features of such terms as “education quality” and “communicative competence” are revealed; the peculiarities of their components and structure are described. Using the results of a survey the authors draw conclusions about the advantages and disadvantages of online and offline learning and the efficacy of technical l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…There were also students who thought that money for online education was wasted. In contrast to students majoring in Philology and Linguistics, the vast majority (57%) are completely satisfied with the quality of online learning (Boyko et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were also students who thought that money for online education was wasted. In contrast to students majoring in Philology and Linguistics, the vast majority (57%) are completely satisfied with the quality of online learning (Boyko et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The experience of the pandemic demonstrated the need to take measures at all levels to prepare current and future teachers for productive professional work in emergencies (Darling-Hammond & Hyler, 2020, Hadar et al, 2020. This applies both to future natural sciences teachers (Ponomareva, 2021;Biletska et al, 2022), philology (Boyko et al, 2021), and others.…”
Section: Literature Reviewmentioning
confidence: 99%
“…-системний, який розглядає ЗВО як сукупність взаємопов'язаних елементів, які взаємодіють та орієнтовані на досягнення конкретної мети в умовах академічного середовища (персоналу, структури, технології); -процесуальний, що аналізує її як неперервну систему взаємодій управлінських функцій; -інформаційний, який передбачає забезпечення керівників і виконавців (менеджмент ЗВО і викладачів) інформацією для прийняття управлінського рішення на рівні університету, факультету, кафедри, академічної групи; -комунікативний, що забезпечує систему встановлення взаємодії для обміну інформацією між усіма учасниками освітнього процесу [13].…”
Section: Quality Management Functions Of Future Teacher Professional ...unclassified
“…Many studies identified neutral or negative effects of changing faceto-face settings to distance format. There is a null difference in education results between the offline settings and blended format (Bowen et al, 2014;Boyko et al, 2021). Many academics point out that the distance format may have negative effects on student performance, taking into consideration grades (Figlio et al, 2013;Means et al, 2010), completion rates (Johnson & Mejia, 2014), and passing test scores (Bowen et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%